The American school of spies : the archaeologists who fought the Nazis and saved the treasures of Ancient Greece - Talty, Stephan (Dutton, 2026)
In 1942, as head of the newly formed OSS, Wild Bill Donovan deployed spies across Europe and around the world to try to thwart the Nazis. In Greece, Nazis weren't just taking over territory; they were seizing and threatening to destroy some of the world's most important and valuable historical monuments and artifacts. So, Donovan tapped a young Ivy League-trained archaeologist named Rodney Young to assemble and lead a team of spies to collect intel. Young set about recruiting the most unlikely of spies-academics, classicists, epigraphers, and other specialists and scholars-who would come to be known as "the Greek Desk." These men and women, along with their Greek allies, went undercover and tried desperately to protect some of the world's most significant treasures. The archaeologists hid priceless artifacts in ancient caves, bank vaults, and even underneath the city of Athens itself. They created fakes to give over to the Nazis to appease their lust for these remarkable works. Ultimately, when it became clear the cat-and- mouse game on its own wasn't going to save Athens, they brought in an army of Greek American soldiers to beat back the Nazi regime and save their homeland.